Towards cultural democracy in mental health: The case of the Mexican-American - Ramirez III, Manual (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Mental health institutions and personnel in general have been insensitive to cultural differences. Cultural differences have been given little consideration in development of personality theories, psychotherapeutic strategies, and psychological tests. An outstanding example of this appeared in the Los Angeles Times a few months ago. A Chinese-American man was committed to a state hospital in California, and was kept there for ten years simply because no one of the staff could speak his Chinese dialect!